Accelerating digital supply chain management practices, customer development, and firm performance: Organizational culture matters - My-Trinh Bui; Don Jyh-Fu Jeng; Huy Hung Ta (Contemporary Economics, 2024)
Firms and suppliers are now using new digital technologies to make decisions for successful strategies. Firms are struggling with the supply chain dynamics needed to increase revenue and mitigate risk, and improve resilience after COVID-19. With the setting of strong competition and firms' business models shifting to digital transformation, this study examines the link between organizational culture (OC) and digital supply chain management practices (DSCMP) in generating a positive impact on firm performance (FP), including both direct and indirect influences via customer development (CD). Smart PLS 3.3.3 was used to analyze data from 326 respondents who registered as business managers who operate their supply chains using digital technol- ogies. The findings indicated that DSCMP, CD, and OC had a favorable impact on FP, while DSCMP and OC had a beneficial impact on CD. It was also determined that DSCMP and CD played a mediating role in both of the above-mentioned associations. DSCMP and OC are two essential enablers for developing a firm's customer base and improving performance efficiency in digital supply chains. Based on the Resource Dependence The- ory (RDT), this study found that digitalization-related capabilities in supply chain management practices must be developed inside the company to improve the firm's efficiency. Firm culture, accompanied by dominant characteristics, organizational leaders, organizational glue, and strategic emphasis should become essential components of DSCMP in organizations.
Keywords: M14; M15; M16; O33; 330; digital supply chain management practices (DSCMP); organizational culture (OC); firm performance (FP); customer development (CD